In silico Approach for Anti-Thrombosis Drug Discovery: P2Y1R Structure-Based TCMs Screening - Yi, Fan; Sun, Le; Xu, Li-jia; Peng, Yong; Liu, Hai-bo; He, Chun-nian; Xiao, Pei-gen (Frontiers in Pharmacology, 2017)
Cardiovascular diseases (CVDs), including thrombosis, which is induced by platelet aggregation, are the leading cause of mortality worldwide. The P2Y1 receptor (P2Y1R) facilitates platelet aggregation and is thus an important potential anti-thrombotic drug target. The P2Y1R protein structure contains a binding site for receptor antagonist MRS2500 within its seven-transmembrane bundle, which also provides suitable pockets for numerous other ligands to act as nucleotide antagonists of P2Y1R. The Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP) comprises 499 Chinese Pharmacopoeia-registered herbs and the structure information for 29,384 ingredients. In silico docking of these compounds into the P2Y1R protein structure within the MRS2500 pocket can identify potential antithrombotic drugs from natural medicinal plants. Docking studies were performed and scored to evaluate ligand-binding affinities. In this study, a total of 8,987 compounds from Traditional Chinese Medicine (TCM) were filtered by Lipinski’s rule of five, and their ideal oral-intake properties were evaluated. Of these, 1,656 compounds distributed in 443 herbs docked into the P2Y1R-MRS2500 structure in 16,317 poses. A total of 38 compounds were ranked with a DockScore above 70, and these may have significant potential for development into anti-thrombosis drugs. These computational results suggested that licorice (Glycyrrhiza uralensis Fisch), cimicifugae (Cimicifuga foetida L.) and ganoderma (Ganoderma Lucidum Karst) and their chemical constituents, which have not previously been widely used for anti-thrombosis, may have unexpected effects on platelet aggregation. Moreover, two types of triterpene scaffolds summarized from ten compounds were distributed in these three herbs and also docked into P2Y1R. These scaffold structures may be utilized for the development of drugs to inhibit platelet aggregation.